Experimental Trypanosoma evansi infection induces pain along with oxidative stress, prevented by COX-2 inhibition - Cipriani, Daniel Sérgio; Borges, Gabriela Kaiser; Povaluk, Ana Paula; Stipp, Maria Carolina; Casagrande, Renata Assis; Vogel, Carla Ivane Ganz; Miletti, Luiz Claudio; Bastos-Pereira, Amanda Leite (Experimental parasitology, 2023)
[Display omitted] •Nonsteroidal anti-inflammatory drugs prevent inflammation, pain and oxidative stress triggered by T. evansi rodent infection.•The inflammation provoked by T. evansi infection in probably mediated by cyclooxygenase-2 and its molecular mediators.•Mice infected by T. evansi show higher presence of vacuolar degeneration of hepatocytes related to oxidative stress damage.•T.evansi infection leads to oxidative stress, affecting both enzymatic and non-enzymatic host protective systems.